An Analysis of President Joko Widodo's Economic Diplomacy from 2014 to 2024: Results in Foreign Investment and Global Trade Volume - Setiawan, Asep (Action Research Literate, 2024)
This research aims to analyze the economic diplomacy strategies undertaken by President Joko Widodo’s administration from 2014 to 2024, focusing on their effectiveness in enhancing Indonesia’s trade volume, attracting foreign direct investment (FDI), and addressing global economic challenges. By examining key initiatives, this study explores the interplay between trade agreements, regulatory reforms, and international partnerships that shaped Indonesia’s economic trajectory. The theoretical framework of this research is rooted in the concept of economic diplomacy, which encompasses the use of economic policies as instruments of foreign policy to advance national interests. Economic diplomacy involves negotiating trade agreements, attracting FDI, and leveraging international partnerships to foster economic growth and geopolitical influence. This study employs qualitative research methods, analyzing secondary data from scholarly journals, government reports, trade and FDI statistics, and publications by international institutions such as the World Bank and the IMF. The findings indicate that President Joko Widodo’s economic diplomacy led to significant advancements in Indonesia’s economic standing. Between 2014 and 2022, Indonesia saw a notable increase in FDI attributed to regulatory reforms such as the Omnibus Law, which simplified business processes and reduced bureaucratic hurdles. Additionally, Indonesia’s active participation in multilateral agreements like the Regional Comprehensive Economic Partnership (RCEP) expanded trade opportunities. This paper contributes to the field of international economic diplomacy by providing a comprehensive analysis of Indonesia’s strategies under President Joko Widodo. It offers valuable insights for policymakers in Indonesia and other emerging economies, demonstrating how domestic reforms, international trade agreements, and strategic partnerships can bolster economic growth.